AKIBAT HUKUM TERHADAP WAJIB PAJAK YANG MELAKUKAN TINDAK PIDANA PERPAJAKAN DITINJAU DARI UU NO. 28 TAHUN 2007 TENTANG KETENTUAN UMUM DAN TATA CARA PERPAJAKAN - NIRWANA DEWI HARAHAP (JURNAL ILMIAH MAKSITEK, 2020)
Corporations in this case can be used as a means to commit criminal acts. One of the supporters of national income is fromtax receipts that account for about 70% of all state revenues. Taxes have a very vital role in a country, without a state living taxwill not be able to go well. Infrastructure development, education costs, health costs, fuel subsidies, payments for stateemployees and the construction of public facilities are all tax-funded. Taxes have normative and historical significance.Normatively, taxes have a legal basis to apply to all citizens and are coercive. Violators of taxes may be subject to legalsanctions. Historically, the understanding and application of taxes followed the development of the history of humancivilization. At first, the tax was understood to be very simple and managed simply as well. As human needs grow and scienceand technology (SCIENCE) advances, tax variations become more diverse as well as more sophisticated management,making it easier for people to pay taxes. A historical approach is indispensable to understanding the current existence(positioning) of taxes. This is necessary for everyone to know that the existence of taxes (in the sense of levies) has beenaround since humans started grouping and making social bonds.